2015
DOI: 10.1088/0953-2048/28/7/072001
|View full text |Cite
|
Sign up to set email alerts
|

Two level undercut-profile substrate for filamentary YBa2Cu3O7coated conductors

Abstract: A novel substrate design is presented for scalable industrial production of filamentary coated conductors (CCs). The new substrate, called 'two level undercut-profile substrate (2LUPS)', has two levels of plateaus connected by walls with an undercut profile. The undercuts are made to produce a shading effect during subsequent deposition of layers, thereby creating gaps in the superconducting layer deposited on the curved walls between the two levels. It is demonstrated that such 2LUPS-based CCs can be produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…A gap is present in the GYBCO layer just below the edge of the upper plateau (marked by "A") that verifies the desired physical decoupling between the superconducting filaments. It was observed that the undercut length L = 1.2 ± 0.5 μm, which is significantly greater, compared to a previously reported Hastelloy-based 2LUPS sample (L=0.3 µm) [14]. In the curved region of the lower plateau (see Fig.2) the GYBCO layer is observed to be both porous and irregular, and as such considered non-functional.…”
Section: B Scanning Electron Microscopymentioning
confidence: 54%
See 3 more Smart Citations
“…A gap is present in the GYBCO layer just below the edge of the upper plateau (marked by "A") that verifies the desired physical decoupling between the superconducting filaments. It was observed that the undercut length L = 1.2 ± 0.5 μm, which is significantly greater, compared to a previously reported Hastelloy-based 2LUPS sample (L=0.3 µm) [14]. In the curved region of the lower plateau (see Fig.2) the GYBCO layer is observed to be both porous and irregular, and as such considered non-functional.…”
Section: B Scanning Electron Microscopymentioning
confidence: 54%
“…Starting from a commercial Hastelloy C276 tape (L×W×T = 300 mm × 10 mm × 0.89 mm), wet electrochemical etching is employed in order to create the desired 2LUPS geometrical profile and to reduce the surface roughness [14].…”
Section: A Samples Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous methods including mechanical scribing [6], [7], laser striation [8]- [10], inkjet printing [11]- [13] and substrate templating [14], [15] have been used to divide CC's into filaments. In the current work an alternative method using high temperature plasma, which occurs during an electrical sparkdischarge between electrode and tape surface, is presented.…”
Section: Introductionmentioning
confidence: 99%